Enantioselective Bifunctional Ammonium Salt‐Catalyzed Syntheses of 3‐CF3S‐, 3‐RS‐, and 3‐F‐Substituted Isoindolinones. Issue 7 (17th February 2021) - Eitzinger, Andreas; Otevrel, Jan; Haider, Victoria; Macchia, Antonio; Massa, Antonio; Faust, Kirill; Spingler, Bernhard; Berkessel, Albrecht; Waser, Mario
Abstract: We herein report the ammonium salt‐catalyzed synthesis of chiral 3, 3‐disubstituted isoindolinones bearing a heteroatom functionality in the 3‐position. A broad variety of differently substituted CF3 S‐ and RS‐derivatives were obtained with often high enantioselectivities when using Maruoka's bifunctional chiral ammonium salt catalyst. In addition, a first proof‐of‐concept for the racemic synthesis of the analogous F‐containing products was obtained as well, giving access to one of the rare examples of a fairly stable α‐F‐α‐amino acid derivative. Abstract :